Comparison of health-promoting lifestyle and irrational health beliefs in healthy pregnant women and gestational diabetes mellitus - Atefe Zeinali; Mahrokh Dolatian; Padideh Janatiataie; Jamal Shams; Malihe Nasiri (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Gestational diabetes mellitus (GDM) is a common complication of pregnancy. The goal of this study was to compare health-promoting lifestyles and irrational health beliefs in pregnant women with GDM and healthy pregnant women. MATERIALS AND METHODS: The present study was a descriptive causal-comparative study in which 100 eligible GDM women and 100 eligible healthy women were selected through available sampling in three referral hospitals in Tehran In 2020. In this study, the Health Promoting Lifestyle Profile (HPLP) and the Irrational Health Beliefs Scale (IHBS) were used. Data were analyzed using independent t-test and logistic regression by SPSS 16 software. RESULTS: Findings showed that there is a significant relationship between the variables of IHBS and HPLP. For every one unit increase in an IHBS score, the chance of having diabetes increases by 2.8%. In the case of HPLP, women who exercised well were 7.5% less likely to develop diabetes, and those who took good responsibility were 7.8% less likely to develop diabetes. Furthermore, in independent t-test, the HPLP variable showed a significant difference between the two groups with diabetes and healthy individuals (P < 0.001). Furthermore, in comparing the subscales of this variable, physical activity (P < 0.0001), self-fulfillment (P < 0.004), responsibility (P < 0.003), and stress control (P < 0.001), a significant difference was observed. The results of IHBS research showed a significant difference between the two groups of gestational diabetes and healthy individuals (P < 0.004). CONCLUSION: The results of the present study show the need to identify and focus on irrational health beliefs and health-promoting lifestyles. Modification of these psychological structures can be useful in the prevention and management of this chronic disease.